The potential of far-red light-acclimating cyanobacteria to support sustainable outposts on Mars - Santos de Sousa, Isabel; Di Stefano, Giorgia; D’Agostino, Andrea; Martella, Costanza Maria; Chirico, Antonio; Rigano, Gabriele; Santo, Loredana; Billi, Daniela (Frontiers in Astronomy and Space Sciences, 2025)
BackgroundLong-duration crewed missions on the Moon and Mars rely on support technologies based on locally available resources. Rock-weathering cyanobacteria are key enablers to transform minerals, carbon dioxide and urine (from crew waste) into biomass to be used to feed heterotrophic bacteria for downstream production of consumables. However, cyanobacterial cultivation in media based on water-released minerals is hindered by reduced light penetration due to the medium turbidity. The biomass production from two desert isolates of Chroococcidiopsis, a strain capable of Far-red Light Photoacclimation (FaRLiP) and a non-FaRLiP strain, was compared to investigate if the former better faced regolith shading.MethodsThe FaRLiP strain CCMEE 010 and non-FaRLiP CCMEE 029 were cultivated for 21 days under VL in Martian water-released minerals with 10 mM urea and 2.4 mM perchlorate and in BG-11 control medium. A comparison was made of cell morphology, photosynthetic pigment emission spectrum and presence of urea transport and catabolism genes.ResultsNo morphological changes occurred among the two strains, but the FaRLiP strain exhibited adaptation to regolith shadowing as shown by an emission peak related to FaRLiP early phase. The absence of pigment bleaching suggested the tolerance towards prolonged cultivation with Mars-relevant perchlorate and urea. The latter was used as a nitrogen source enabled by genes for urea transport and catabolism. Biomass lysates from both strains supported the growth of heterotrophic bacteria, although the FaRLiP-positive strain cultivated in both Martian water-released minerals and BG-11 medium accumulated more biomass and thus promoted greater bacterial growth.ConclusionThe cultivation under VL with Martian water-released minerals (with perchlorate and urea) showed that the FaRLiP strain suffered less growth detriment in the turbid medium, though the potential role of this process in Bio-ISRU remains unclear.